105k views
3 votes
21 and 23 please explained

21 and 23 please explained-example-1

1 Answer

6 votes

A function
f(x) is
odd, when
f(-x)= -f(x) and
even when
f(-x)= f(x)

21. Given function:
y= 1- cos(x) or
f(x)= 1-cos(x)

So,
f(-x)= 1-cos(-x) = 1- cos(x) = f(x)

As here
f(-x)= f(x), so the function will be Even function.


23. Given function:
y=f(x)= (x^4 +1)/(x^3-2x)

So,
f(-x)= ((-x)^4 +1)/((-x)^3 -2(-x))= (x^4 +1)/(-x^3+2x)=(x^4+1)/(-(x^3-2x))=-(x^4+1)/(x^3-2x)=-f(x)

As, here
f(-x)= -f(x), so the function will be Odd function.

User PhonicUK
by
5.4k points